2011
DOI: 10.1017/s026841601100004x
|View full text |Cite
|
Sign up to set email alerts
|

Women's clothes and female honour in early modern London

Abstract: This article explores how the reputations and agency of middling and plebeian women in sixteenth- and seventeenth-century London were affected by what they wore. Compared with provincial England, markets for women's clothes in the capital were more diverse and accessible. Ambiguous moral judgments were made of women based on their dress, but many sought to acquire good, fashionable attire as the right clothes would improve their options in terms of courtship, sociability and employment, as well as facilitating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Wallis and Webb cite her work regarding the education of younger sons of the gentry, while Harrington praises her research into the sales of Royalist lands during the Interregnum. Dean uses Thirsk's work on Elizabethan financial projects, and Thirsk's research into consumption goods is cited by Reinke‐Williams. Thirsk's pioneering research into agrarian history is used extensively by Clark, and also by Shepard and Spicksley.…”
Section: –1700mentioning
confidence: 99%
See 2 more Smart Citations
“…Wallis and Webb cite her work regarding the education of younger sons of the gentry, while Harrington praises her research into the sales of Royalist lands during the Interregnum. Dean uses Thirsk's work on Elizabethan financial projects, and Thirsk's research into consumption goods is cited by Reinke‐Williams. Thirsk's pioneering research into agrarian history is used extensively by Clark, and also by Shepard and Spicksley.…”
Section: –1700mentioning
confidence: 99%
“…The importance of dress and appearance for women is discussed by both Reinke‐Williams and by Poitevin. Reinke‐Williams considers the use of clothing as a Veblen good which signified status. He also considers the use of sumptuary legislation to attempt to regulate the London clothing market in the sixteenth and seventeenth centuries.…”
Section: –1700mentioning
confidence: 99%
See 1 more Smart Citation
“…21 Tim Reinke-Williams has also shown how women's clothing changed with their marital status: young unmarried women went bareheaded, while those who had experienced marriage wore distinctive scarves and hoods. 22 According, Froide has suggested that married women and widows should be classified as "ever-married" women, a term that recognized their social ties through the experience of marriage. However, the judicial system did not treat married women and widows (that is, "ever-married" women) in a similar manner.…”
mentioning
confidence: 99%
“…In a city where appearances mattered greatly, a man's reputation depended as much on what his wife and daughters worenot least because it was most often he that footed the billas on the quality and cut of his own outfit. 56 But consumption was not just about status and hierarchy; it was also concerned with symbolic communication between individuals and groups. 57 Goods acquired value in a shared system of meaning and played an important role as symbols of belonging in social networks.…”
mentioning
confidence: 99%